Effectiveness of Social Media in Enhancing the Conceptual Development - Kifayat Ullah ,; Dr. Saqib Shehzad,; Dr Hafiz Muhammad Irshad Ullah,; Azmat Ali Shah, (Dialogue Social Science Review (DSSR), 2024)
The study was conducted to determine the effectiveness of social media in enhancing individual’s conceptual development at university level in Khyber Pakhtunkhwa, Pakistan. Objectives of the study were to identify the effectiveness of social media in enhancing individual’s ability to remember, understand and apply concepts. The study was descriptive (quantitative) in nature. The survey research method was used to collect quantitative data from the respondents. The population of the study comprises students from the department of education at public sector universities of Khyber Pakhtunkhwa. Purposive sampling technique was used for the selection of the sample. Four hundred (400) students/scholars from ten (10) universities, forty (40) respondents from each university. Data were collected from five (5) public sector universities, three (3) private sector universities, and two women's universities in the Khyber Pakhtunkhwa. Based on findings it was concluded that most students responded that social media is an effective platform to enhance an individual’s ability to define terms, share, recall, and assess information by using different applications of social media in different ways i.e. lectures, maps, diagrams, videos, related films, news, information and book etc. Majority of the sample responded that social media is vital in enhancing the learners’ ability to judge, explain, compare, classify, and create phenomena. A maximum number of students responded that social media applications enable individuals to modify, choose, and use information in new, continuously changing situations. Most students responded that social media is an effective tool to enhance students’ ability to order, analyze, criticize, and differentiate concepts. Most students responded that social media effectively enhances an individual’s ability to summarize, judge, and evaluate teachers. Majority students responded that social media is an effective platform to enhance an individual’s ability to develop, create, design, modify, propose, and invent concepts.